2013
DOI: 10.5846/stxb201202130189
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the carbon cycle ofLarix chinensisforest during 1958 and 2008 at Taibai Mountain, China

Abstract: 年间太白红杉南北坡 NPP 的平均值为 0. 38 kgC•m-2 •a-1 ,巴山冷杉为 0. 25 kgC•m-2 •a-1 ,两者之和占整个太白 红杉林 NPP 的 86% ;1958-2008 年间太白红杉南北坡生物量的平均值为 2. 91 kgC / m 2 ,巴山冷杉为 2. 02 kgC / m 2 ,两者之和占 太白红杉林生物量的 94% 。 2) 太白红杉和巴山冷杉的 NPP 均表现为北坡大于南坡,且南北坡均有逐年增加的趋势,北坡的增 幅小于南坡,所以太白山南北坡太白红杉林的 NPP 差异有逐年减少的趋势。 3) 太白红杉生物量的年际波动较大,南北坡呈交 替上升趋势,南坡的平均值(2. 94 kgC / m 2) 大于北坡(2. 89 kgC / m 2) 。 巴山冷杉生物量的年际波动相对较小,北坡生物量水平 大于南坡。 4)1958-2008 年南北坡太白红杉林平均 NEE 均为-0. 023 kgC•m-2 •a-1 ,表现为碳汇。 南北坡碳汇水平均呈逐年增 加趋势,南坡的增加幅度(0. 91 g•m-2 •a-1) 大于北坡(0. 42 g•m-2 •a-1) 。 以气候和 CO 2 为驱动… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Li et al found that the average NPP was 305.33 gCm -2 a -1 using the BIOME-BGC model to study the Taibai Redwood on the northern slope of the Qinling Mountains [29] . Li et al simulated an average NPP of 380 gCm -2 a -1 from 1958 to 2008 based on LPJ-GUESS, a vegetation dynamic process model [30] . Zhang et al used the BIOME-BGC model to simulate the Taibai Redwood on the northern slope of the Qinling Mountains, with the NPP of 328.59 gCm -2 a -1 from 1959 to 2016 [31] .…”
Section: Results Comparison Verificationmentioning
confidence: 99%
“…Li et al found that the average NPP was 305.33 gCm -2 a -1 using the BIOME-BGC model to study the Taibai Redwood on the northern slope of the Qinling Mountains [29] . Li et al simulated an average NPP of 380 gCm -2 a -1 from 1958 to 2008 based on LPJ-GUESS, a vegetation dynamic process model [30] . Zhang et al used the BIOME-BGC model to simulate the Taibai Redwood on the northern slope of the Qinling Mountains, with the NPP of 328.59 gCm -2 a -1 from 1959 to 2016 [31] .…”
Section: Results Comparison Verificationmentioning
confidence: 99%